Modeling and testing the steady-state and transient behaviors of stacked microbial fuel cells under different electrical connection patterns. (25th December 2022) - Di Micco, S.; De Falco, P.; Bracale, A.; Caramia, P.; Minutillo, M.
Abstract: Microbial fuel cells (MFCs) represent a key solution in the context of sustainable energy development from organic material. Their implementation for real applications is still limited because of economic issues and low power densities. Several efforts have been done both to improve the economic performances by selecting low-cost materials and to increase the power output by realizing stacked configurations. The development of more complex configurations increases the difficulty of predicting the behavior of these bioenergy systems and their performances. In this contest numerical models, supported by the experimental activities, are very useful tools for forecasting the main biological, electrochemical and mass transfer processes occurring within MFCs during their operation in different conditions. In this paper, an electrical transient model, devoted to perform the stacked MFCs voltages and currents on equivalent electric circuits has been developed. The model, that is the superposition of an exponential pattern over a linear trend, is able to define the transient time domain of the voltage and current solutions of a specific electric circuit, enabling the scalability of the estimation of the electrical variables in stacked MFCs systems. The model calibration has been carried out by means of the experimental activities on a single MFC reactor as well as on a stacked MFCs configuration connected in parallel/series. The experimental activities have been performed by using a test bench consisting of the Agilent Digit Multimeters and a Resistance Box. The experimental tests have allowed to assess: i) the steady-state and transient behaviors of a single MFC; ii) the steady-state and transient behaviors of the stacked MFCs configurations. Results have highlighted that the developed model has proved to be an interesting tool for predicting the transient behavior of output currents and voltages after a step perturbation demonstrating how the MFCs evolve towards stable conditions as the load varies. Highlights: The development, modeling and testing of MFCs stacked configurations is proposed. Configurations based on series and parallel/series electric connections are studied. An electrical model for assessing the stacked MFCs transient behavior is set up. The steady-state behavior of the MFCs with the direct monocyclic method is assessed. The steady-state behavior of the MFCs with the inverse monocyclic method is studied.